The persistence of maternal vitamin D deficiency and insufficiency during pregnancy and lactation irrespective of season and supplementation. (11th February 2016) - Kramer, Caroline K.; Ye, Chang; Swaminathan, Balakumar; Hanley, Anthony J.; Connelly, Philip W.; Sermer, Mathew; Zinman, Bernard; Retnakaran, Ravi
Summary: Background: Pregnancy and lactation comprise a critical window spanning all seasons during which maternal vitamin D status potentially may influence the long‐term health of the newborn. Women typically receive calcium/vitamin D supplementation through antenatal vitamins, but there has been limited serial evaluation of maternal vitamin D status across this critical window. Design/Patients/Measurements: In this prospective observational cohort study, 467 women in Toronto, Canada, underwent measurement of serum 25‐hydroxy vitamin D (25‐OH‐D) at mean 29·7 ± 2·9 weeks' gestation, 3 months postpartum and 12 months postpartum, enabling serial assessment across 3 seasons. At each assessment, vitamin D status was classified as deficiency (25‐OH‐D<50 nmol/l), insufficiency (25‐OH‐D≥50 nmol/l and <75 nmol/l) or sufficiency (25‐OH‐D≥75 nmol/l). Results: The prevalence rates of vitamin D deficiency and insufficiency were 31·5% and 35·1% in pregnancy, 33·4% and 35·3% at 3 months, and 35·6% and 33·8% at 12 months postpartum, respectively. These high rates remained stable over time ( P = 0·49) despite declining usage of antenatal calcium/vitamin D supplementation from pregnancy to 3 months to 12 months postpartum ( P < 0·001). Indeed, on mixed model analyses, vitamin D deficiency and insufficiency in pregnancy were independently associated with decrements in average 25‐OH‐D over time of 49·6 nmol/l and 26·4 nmol/l, respectively (both P < 0·001). In contrast, season of baseline assessment and use of calcium/vitamin D supplements were independently associated with changes in 25‐OH‐D in the range of 3–5 nmol/l (both P < 0·008). Conclusions: The persistence of vitamin D deficiency/insufficiency during pregnancy and lactation, irrespective of season and supplementation, supports the emerging concept that current vitamin D supplementation in antenatal care is likely inadequate.